Advances in Nondestructive Methods for Meat Quality and Safety Monitoring. Issue 6 (18th August 2019) - Kutsanedzie, Felix Y. H.; Guo, Zhiming; Chen, Quansheng
ABSTRACT: Meat is highly perishable and poses health threats when its quality and safety is unmonitored. Chemical methods of quality and safety determination are expensive, time-consuming and lack real-time monitoring applicability. Nondestructive techniques have been reported as antidotes to these constraints. This paper assessed the potential of nondestructive techniques such as near-infrared spectroscopy, hyperspectral imaging, multispectral imaging, e-nose, and their data fusion, all combined with algorithms for quality monitoring of pork, beef, and chicken, the most consumed meat sources in the world. These techniques combined with data processing applications may offer a panacea for real-time industrial meat quality and safety monitoring.